Combined effects and potential mechanisms of volatile organic compounds on thyroid disease in the US population: An integrated epidemiological and computational toxicology study - Qun Lu; Zhilei Mao; Yanling Chen; Kun Zhou (Ecotoxicology and Environmental Safety)
Objective: Our study aims to investigate the association between blood VOCs and thyroid diseases in US population and reveal the underlying mechanisms. Methods: NHANES 2011–2016 data were used to explore the association between blood VOC levels and thyroid disease through Weighted Quantile Sum (WQS) regression, logistic regression, and smooth curve fitting. Dibromochloromethane-related and thyroid disease targets were obtained from TargetNet, SuperPred, GeneCards, and GEO. A protein-protein interaction (PPI) network was constructed using STRING, and GO/KEGG enrichment analyses were performed using DAVID. Molecular docking and core target validation were carried out with Autodock Vina 1.1.2, GEPIA, and HPA databases. Results: After adjusting for covariates, higher levels of blood Dibromochloromethane and Chloroform were associated with higher risks of thyroid disease (p < 0.05). We also found nonlinear associations of Dibromochloromethane and Chloroform levels with risk of thyroid disease at lower concentrations (p < 0.05). Ten proteins were identified as core targets for the effects of Dibromochloromethane on thyroid disease, and mainly enriched the Apelin, HIF-1, and Thyroid hormone signaling pathways. External validation revealed upregulation of CTSB, PLAT, and MTOR, and downregulation of SERPINE1, NOS3, with SLC9A1 and XDH being associated with thyroid carcinoma stage. Conclusion: Positive associations between blood Dibromochloromethane and Chloroform levels and thyroid disease were observed. Dibromochloromethane interacts with core targets such as MTOR, NOS3, and SLC9A1, influencing thyroid disease progression. With the widespread exposure to VOCs worldwide, this will deepen and enrich our understanding of the potential mechanism of Dibromochloromethane in thyroid disease and provide a theoretical basis for subsequent studies.